Identifying Faculty Members Motivation Factors in Tehran Payame Noor University - Feizy Feizy (مدیریت دولتی, 2013)
Identifying motivation factors is one of the best ways to release faculty’s energies toward active participation in research and educational affairs. In this regard, an applied research based on survey strategy conducted using 453 sample sizes from formal and visiting faculty members of Payame Noor as a distance education university. By literature review and some interviews with educational experts, a forty-eight item questionnaire was developed and sent to faculty members. In one hand, Confirmatory factor analysis showed that firstly it can cast 48 items in 10 factors, namely: identity, promotion and advancement, responsibility, participation, communication, security and welfare, rewards, work conditions, policy and procedure, and quantity and quality of students. Secondly, these 10 factors are explained well by two-dimensional motivation construct: intrinsic and extrinsic. At the other hand, mean test results indicated that promotion and advancement is the most important factor in faculty members’ motivation. In addition, faculty members in current state have high satisfaction with identity factor. The major theoretical contribution of this research is that intrinsic factors have important role in faculty members’ motivation.